Aizat Mohd Nasir, outstanding young alumnus, receives UMPSA 2024 Mercu Sanjung Alumni Hope Award - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
GAMBANG, 16 April 2025 – The commitment and outstanding contributions of a young alumnus of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Aizat Mohd Nasir, paid off when he was named as the recipient of the UMPSA 2024 Mercu Sanjung Alumni Hope Award during the Mercu Sanjung Awards Night (MARS) recently held at the UMPSA Gambang Campus Sports Complex Hall.